Modelling of pH effects and CIE L*a*b*colour spaces of beech wood-inhabiting fungi by NIRS. Issue 4 (8th August 2018) - Koumbi-Mounanga, Thierry; Tudor, Daniela; Leblon, Brigitte; Groves, Kevin; Cooper, Paul A.; Ung, Tony
ABSTRACT: A combination of statistical techniques of analyses were used to evaluate the potential of International Commission on Illumination (CIE) lightness (L*), redness (a*) and yellowness (b*) colour space system and near-infrared spectroscopy (NIRS) to assess surface changes in relation with progressive decay of beech ( Fagus grandifolia Ehrh.) by wood-inhabiting lignicolous fungi Inonotus hispidus, Trametes versicolor and Xylaria polymorpha . pH effects based modelling predictions of beech earlywood and latewood tissues were also included. Multivariate analysis techniques included response surface optimization, sample-specific standard error of prediction (SEP) method and projection to latent structures partial least squares (PLS) regression. Strong statistical relationships were derived for pH predictions with R 2 values ranged: from 0.77 to 0.84 for I. hispidus ; from 0.77 to 0.84 for T. versicolor and from 0.83 to 0.91 for X. polymorpha . R 2 values for CIE-based L*a*b* colour space measurements ranged: from 0.43 to 0.69 (L*), 0.66 to 0.76 (a*), 0.42 to 0.53 (b*) for I. hispidus ; from 0.59 to 0.69 (L*), 0.69 to 0.79 (a*), 0.64 to 0.79 (b*) for T. versicolor ; and from 0.51 to 0.75 (L*), 0.89 to 0.94 (a*), 0.85 to 0.89 (b*) for X. polymorpha . Multivariate technical analysis (response surface analysis, sample-specific SEP, PLS regression) of CIE L*a*b* system and NIRS results should be able to characterize pH effects and surface changes of wood spalted by lignicolous fungi as a quick and reliable non-destructive method relevant to wood-spalting concerns and the forest products industry.